Hoarding Disorder: A Case Report - Vilaverde, Daniela; Gonçalves, Jorge; Morgado, Pedro (Frontiers in Psychiatry, 2017)
Hoarding disorder is characterized by a persistent difficulty discarding items, the desire to save items to avoid negative feelings associated with discarding them, significant accumulation of possessions that clutter active living areas and significant distress or impairment in areas of functioning. We present a case of a 52-year-old married man, who was referred to the psychiatry department for collecting various objects that were deposited unorganized in the patient’s house. He reported to get anxious when someone else discarded some of these items; This behavior had started about 20 years earlier and it got worse with time. The garage, attic and surroundings of his house were cluttered with these objects. On admission, in the mental status examination, the patient was vigil, calm and oriented. His mood was depressed. His speech was organized, logic and coherent. There were not psychotic symptoms. A psychotherapeutic plan for the patient was designed, including psychoeducation, cognitive restructuring and exposure to discarding objects. A pharmacological treatment with Fluvoxamine 100mg tid and Quetiapine 200mg was added to the therapeutic plan, with the progressive improvement of the symptoms. Nine months later, the patient was able sell/recycle most of the items. Studies evaluating treatment for Hording Disorder are necessary to improve the quality of life of the patients and reduce the hazards associated with the disorder.